The relationship between women earning potential, household responsibilities, workplace environment and financial need towards women work-life conflicts at head quarters of Pengurusan Air Pahang Berhad, Kuantan / Izzatul Fitrah Abdul Wahab - Abdul Wahab, Izzatul Fitrah (Faculty of Business and Management, 2019)
Women work-life conflict occurred when they need to balance between career responsibilities with home responsibilities. Women were pressured to have commitment with domestic industry in order to fulfill their families' need due to high cost of living. Hence, the purpose of the study was to identify the relationship between women earning potential, household responsibilities, workplace environment and financial need with work-life conflict. The study described the factors that correlate with work-life conflict at Head Quarters of Pengurusan Air Pahang Berhad Kuantan. The questionnaire used in this study was retrieved from previous study then distributed manually using simple random sampling technique to women employees at the company. By referring to Krejcie and Morgan table (1970), the scopes were focused on the certain number of population. The sample sizes were taken referred to the sample size for a given population. As the company has 87 women employees thus the sample size for the study is 73 respondents. Then, the data will be analyzed and interpreted using SPSS software. The data analysis had come out with findings of the study. The study found that workplace environment had the most significant relationship with work-life conflict. In addition, as correlation analysis was done, the study found that there is relationship between women earning potential, workplace environment and financial need with worklife conflict. However, there is no relationship between household responsibilities with work-life conflict. Thus, three hypotheses were accepted; women earning potential, workplace environment and financial need while one hypothesis was rejected; household responsibilities. Moreover, it clearly determined that the respondents' background did not affect the relationship between women earning potential, household responsibilities, workplace environment and financial need towards work-life conflict. There were some recommendations provided for the company and for future research. It is suggested for the company to encourage the manager to be close with the employees and be more supportive towards them. In addition, the company might considered flexible work hours for the employees. Secondly, the researchers were recommended to develop another study about identifying the most factors that influence women work-life at the company by using multiple regression analysis. Thus, the company can beware of the factors to avoid serious work-life conflict among women employees. Thirdly, the researcher can carry out a different study by developing another dependent variable such as job tum over instead of existed dependent variable, work-life conflict. From the study, they can conduct another study from work-life conflict to job tum over.